Utilização de extrato tânico comercial como retardante de fogo em madeira - Barros, Jeinna Michelly Rodrigues de (2022)
Despite being a material used in civil construction, wood still lacks reliability to expand it is use, largely due to the lack of knowledge about its thermal properties when exposed to fire. Because it is a flammable material, treatment with fire retardants is necessary to increase confidence in its use. More sustainable products, such as tannin, are an alternative to the products commonly used for this purpose. Therefore, this work aimed to evaluate the use of a tannic extract as a fire retardant in wood. For the analysis, the wood of Simarouba amara Aubl. species was used, and the treatments were given with a commercial retardant, the tannic extract, and a varnish. The colorimetric parameters were determined, such as luminosity, the chromatic coordinates of green-red and yellow-blue, saturation and tone angle, and the difference in coloration after the treatment of the samples. Both materials, treated and control samples were characterized using thermogravimetric analysis. Through the short exposure burning test, the ignition (IT), flame (FT) and ember (ET) times and the residual mass after burning were determined, in addition to the analysis of the carbonized layer. All the materials used influenced the colorimetric parameters, however, the tannic extract was the material that most influenced the coloration and the commercial retardant, the mass retention. The best results with commercial retardant and tannic extract were obtained by the immersion method. For coloration, the most expressive treatment was the one with tannin and varnish (TVP), with the total color variation classified as very appreciable. The commercial retardant provided the highest mass retention, having for the immersion treatment (OI), a value of (35.64%), and the lowest for the treatment with tannic extract (TI), with (0.71%). The temperature of the degradation peak of the tannic extract at 600 °C was higher than that observed for the untreated sample, which occurred at 320 °C. All treatments influenced the reduction of mass loss, although it was more significant in the treatments with the commercial retardant. As with the commercial retardant, the treatment of the samples with tannic extract, in addition to reducing the ignition (IT), flame (FT), and ember (ET) times, resulted in an increase in residual mass after the burning test. In comparison with the untreated sample, the treatment with tannic extract by immersion resulted in a reduction in the ember time (ET), ten times less than that observed for the control (CR), in addition to increasing the residual mass by two times. In all treated samples, the carbonized layer promoted an isolation, protecting the interior of the wood. We conclude that the tannic extract has shown potential for use as a fire retardant in wood.